1997
DOI: 10.1002/hep.510250633
|View full text |Cite
|
Sign up to set email alerts
|

A hepatitis B virus mutant with a new hepatocyte nuclear factor 1 binding site emerging in transplant-transmitted fulminant hepatitis B

Abstract: chronic HBV infection is thought to be immune-mediated, a Hepatitis B virus (HBV) DNA was cloned from serum direct cytopathic role for HBV is postulated in immunosupof a heart transplant recipient who died from fulminant pressed transplantation recipients, especially in patients hepatitis B transmitted by the donor. Restriction enwith histological features of fibrosing cholestatic hepatitis 1 zyme analyses of the clones obtained by conventional and steatoviral or fibroviral hepatitis B.2 In these patients clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
77
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 15 publications
(18 reference statements)
5
77
0
Order By: Relevance
“…Previous studies reporting single cases or reports that focused on subgenomic regions suggested that deletions/insertions in Cp/EnII, deletions in the C gene, and deletions in the pre-S region might be associated with an unfavorable outcome of infection. [5][6][7] These studies were extended here by investigating a large number of patients in comparison with a control group as well as by analyzing complete HBV genomes by PCR and full-length genome cloning. An association between the clinical course and presence of mutations in HBV was studied cross-sectionally and longitudinally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reporting single cases or reports that focused on subgenomic regions suggested that deletions/insertions in Cp/EnII, deletions in the C gene, and deletions in the pre-S region might be associated with an unfavorable outcome of infection. [5][6][7] These studies were extended here by investigating a large number of patients in comparison with a control group as well as by analyzing complete HBV genomes by PCR and full-length genome cloning. An association between the clinical course and presence of mutations in HBV was studied cross-sectionally and longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…The latter have been shown to enhance the pregenomic RNA and core protein levels in vitro. 5,11 This might be a prerequisite for efficient complementation of C gene deletion variants, which fully depend on the supply of functional core protein in trans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations